Immune cells and Notch1 signaling appear to drive the epithelial to mesenchymal transition in the development of adenomyosis in mice. (31st August 2021) - Bourdon, M; Santulli, P; Doridot, L; Jeljeli, M; Chêne, C; Chouzenoux, S; Nicco, C; Marcellin, L; Chapron, C; Batteux, F
Abstract: The epithelial to mesenchymal transition (EMT) has been implicated in the development of adenomyosis, along with dysregulated immune responses. Inflammation potentially induces Notch signaling, which could promote this EMT. The objective of this study was to investigate the involvement of immune cells and Notch1-mediated EMT in the development of adenomyosis. Adenomyosis was induced in 18 CD-1 mice by neonatal oral administration of tamoxifen (TAM group), while 18 neonates received vehicle only (Control group). Their uteri were sampled at 30, 60 or 90 days of age. Immune cell markers ( Cd45, Ly6c1, Cd86, Arginine1, Cd19, Cd4, Cd8 ), Notch1 and its target genes ( Hey1, Hey2, Hes1, Hes5 ) and biomarkers of EMT ( E-Cadherin, Vimentin, Tgfb, Snail1, Slug, Snail3 ) were analyzed by quantitative RT-PCR and immunohistochemistry. Activated-Notch1 protein was measured by western blot. Aberrant expression of immune cell markers was observed in the uteri of mice as they developed adenomyosis. The expression of inflammatory cell markers, notably M1 macrophages and natural killer cells, was increased from Day 30 in the TAM group compared to controls, followed by an increase in the Cd4 marker (T cells) at Day 60. Conversely, expression of the Cd19 marker (B cells) was significantly reduced at all of the stages studied. Notch1 signaling was also highly activated compared to controls at Day 30 and Day 60. Concomitantly, the levels of several markers for EMT were also higher. Therefore, the activation of Notch1 coincides with aberrant expression of immune and EMT markers in the early development of adenomyosis.